Specifics of State Structures of the Mongol Empire - SYZDYKOVA, Zhibek; KOBLANDIN, Kalybek (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT In the course of the study, it has been determined that the main reasons that contributed to the emergence of the Mongol empire are related to its rather dynamic and progressive development, which at the same time relied on the traditional institutions of nomadic people. It should be noted that the features of the supreme power of the empire and the ways of its implementation are often associated with the features of its territorial structure, the nature of relations between the central imperial power and peripheries of different status; this emphasizes the specificity of the organization of the Mongol empire. RESUMEN En el curso del estudio, se determinó que las principales razones que contribuyeron al surgimiento del imperio Mongol están relacionadas con su desarrollo dinámico y progresivo, que al mismo tiempo dependía de las instituciones tradicionales de pueblos nómadas. Cabe señalar que las características del poder supremo del imperio y las formas de su implementación a menudo se asocian con las características de su estructura territorial, la naturaleza de las relaciones entre el poder imperial central y las periferias de diferente estatus; esto enfatiza la especificidad de la organización del imperio Mongol.